Does it pay to park in front of a fire hydrant?. Issue 1 (10th February 2023) - Andrade, Chris; Auerbach, Jonathan; Bacelar, Icaro; Lee, Hane; Tan, Angela; Vazquez, Mariana; Ward, Owen
Abstract: You're a New York motorist, running horribly late, and there's an empty space beckoning right outside your destination. Problem is, it's in front of a fire hydrant. Should you risk getting a ticket? Take some advice from Chris Andrade, Jonathan Auerbach, Icaro Bacelar, Hane Lee, Angela Tan, Mariana Vazquez, and Owen Ward Abstract : You're a New York motorist, running horribly late, and there's an empty space beckoning right outside your destination. Problem is, it's in front of a fire hydrant. Should you risk getting a ticket? Take some advice from Chris Andrade, Jonathan Auerbach, Icaro Bacelar, Hane Lee, Angela Tan, Mariana Vazquez, and Owen Ward